2011
DOI: 10.3171/2011.1.spine10426
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after incidental durotomy during first-time lumbar discectomy

Abstract: Object Incidental durotomy is an infrequent but well-recognized complication during lumbar disc surgery. The effect of a durotomy on long-term outcomes is, however, controversial. The authors sought to examine whether the occurrence of durotomy during surgery impacts long-term clinical outcome. Methods Spine Patient Outcomes Research Trial (SPORT) participants who had a confirmed diagnosis of interverteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 29 publications
5
57
0
Order By: Relevance
“…One limitation of the SPORT, and therefore this study, is the high crossover rate observed between the operative and nonoperative groups. However, because previous authors found consistencies between cohorts, the data have been combined into an as-treated analysis in many of the studies included in this review [3,5,6,8,9,11,[14][15][16][17][18]. Also, the 8-year followup rate was 63% of the initial subjects, and baseline demographics tended to be favorable to a better outcome in both the surgical and nonoperative groups [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One limitation of the SPORT, and therefore this study, is the high crossover rate observed between the operative and nonoperative groups. However, because previous authors found consistencies between cohorts, the data have been combined into an as-treated analysis in many of the studies included in this review [3,5,6,8,9,11,[14][15][16][17][18]. Also, the 8-year followup rate was 63% of the initial subjects, and baseline demographics tended to be favorable to a better outcome in both the surgical and nonoperative groups [10].…”
Section: Discussionmentioning
confidence: 99%
“…Search criteria included ''SPORT'' AND ''disc'' AND ''Spine Patients Outcomes Research Trial,'' which returned 36 articles. Of these, we identified 11 articles that analyzed subgroups of the SPORT patients with IDH [3,5,6,8,9,11,[14][15][16][17][18] (Table 1). A listing of SPORT-related Table 1.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…
of arthrodesis is exceedingly rare [6][7][8][9]. We present a case of acute SSDH, presenting with cauda equina after surgical decompression and reconstruction, as well as summarize the current literature on SSDH.
Case Report

A 72 year old man presented with lower back pain extending down the left anterior thigh, one year after an uncomplicated L2-5 laminectomy for lumbar spinal stenosis.

…”
mentioning
confidence: 99%
“…of arthrodesis is exceedingly rare [6][7][8][9]. We present a case of acute SSDH, presenting with cauda equina after surgical decompression and reconstruction, as well as summarize the current literature on SSDH.…”
mentioning
confidence: 99%